Adalimumab-Adbm: The First Interchangeable Biosimilar for the Treatment of Inflammatory Diseases. Issue 12 (December 2022) - Bhat, Shubha; Patel, Maitri; Duly, Kristine; Choi, David
Objective: The objective of the study was to review the pharmacologic and clinical profile of adalimumab-adbm (BI 695501), the first interchangeable biosimilar for treatment of inflammatory diseases. Data Sources: A PubMed search was conducted from inception to December 2021 using the keywords BI 695501 and adalimumab-adbm . Information was also obtained from published abstracts and package inserts. Study Selection and Data Extraction: Phase 1, 2 and 3 studies plus relevant literature on adalimumab-adbm pharmacologic and clinical profile were reviewed. Data Synthesis: Adalimumab-adbm approval was based on a series of phase 3 VOLTAIRE trials, which evaluated the biosimilar's efficacy and safety in the treatment of moderate to severe Crohn's disease, rheumatoid arthritis, and psoriasis. Interchangeability status was granted based on data from the VOLTAIRE-X trial. The VOLTAIRE and VOLTAIRE-X studies demonstrated comparable efficacy and safety between adalimumab-adbm and reference adalimumab. Common adverse events included infections and injection site reactions. Similar to reference adalimumab, adalimumab-adbm contains black box warnings related to serious infections and malignancy. Relevance to Patient Care and Clinical Practice: Adalimumab-adbm is the first interchangeable biosimilar to be approved for inflammatory diseases and has the potential to improve patient access to treatment while decreasing medication-related costs. However, it will not be commercially available for patient use until 2023 and its adoption into clinical practice may face potential barriers seen with other biosimilars. Conclusion: As an interchangeable biosimilar with comparable efficacy and safety to reference adalimumab, adalimumab-adbm is an important advance toward cost-effective management of inflammatory diseases.